The Influence Of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, And Financial Literacy On Use Behavior Of Buy Now Pay Later Services With Behavior Intention As A Mediating Variable Among Generation Z In The Bandung Raya Area - refsi, Firdaus; Mukti Soma, Abdul (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Growing presence of Buy Now Pay Later (BNPL) services has significantly influenced the way consumers conduct digital transactions. Generally structured as short-term, interest-free credit, these services have rapidly gained traction—especially among younger generations in Indonesia, BNPL services have been on the rise, with significant growth in the number of contracts signed for these services. According to the Financial Services Authority (OJK) report (2023) the number of BNPL contracts in Indonesia reached nearly 80 million in 2023, showing an average annual growth rate of 144.35% in the last five years. This research aims to analyze the factors that influence young people, especially Generation Z, in adopting buy now pay later services. In addition, research was conducted to examine the factors that influence user behavior using the Unified Theory of Acceptance and Use of Technology (UTAUT) theory with the addition of Financial literacy variables. This research uses descriptive research with quantitative methods. The research sample was obtained using 400 respondents. Data was obtained through questionnaires distributed to Gen Z in Greater Bandung. The data was then analyzed with the Statistical Package for Social Science (SPSS). The results showed that the variables of effort expectancy, social influence, and financial literacy have a significant influence on behavior intention. Furthermore, performance expectancy, financial literacy and behavior intention have a significant effect on use behavior. Based on the results of mediation testing, social influence and financial literacy have a significant effect on use behavior through behavior intention as a mediating variable.